Rare Compound Heterozygous Frameshift Mutations in ALMS1 Gene Identified Through Exome Sequencing in a Taiwanese Patient With Alström Syndrome - Tsai, Meng-Che; Yu, Hui-Wen; Liu, Tsunglin; Chou, Yen-Yin; Chiou, Yuan-Yow; Chen, Peng-Chieh (Frontiers in Genetics, 2018)
Alström syndrome (AS) is a rare autosomal recessive disorder that shares clinical features with other ciliopathy-related diseases. Genetic mutation analysis is often required in making differential diagnosis but usually costly in time and effort using conventional Sanger sequencing. Herein we describe a Taiwanese patient presenting cone-rod dystrophy and early-onset obesity that progressed to diabetes mellitus with marked insulin resistance during adolescence. Whole exome sequencing of the patient’s genomic DNA identified a novel frameshift mutation in exons 15 (c.10290_10291delTA, p.Lys3431Serfs*10) and a rare mutation in 16 (c.10823_10824delAG, p.Arg3609Alafs*6) of ALMS1 gene. The compound heterozygous mutations were predicted to render truncated proteins. This report highlighted the clinical utility of exome sequencing and extended the knowledge of mutation spectrum in AS patients.